2021
DOI: 10.3390/bioengineering8120219
|View full text |Cite
|
Sign up to set email alerts
|

Attenuating Effect of Vitamin E against Silver Nano Particles Toxicity in Submandibular Salivary Glands

Abstract: Silver nanoparticles (AgNPs) are extensively used in many industries due to their superior antimicrobial properties. However, it is evident from many studies that AgNPs has cytotoxic potential through its effect on excessive formation of reactive oxygen species (ROS). The aim of this study was to examine the toxic effect of AgNPs on the submandibular salivary glands and the attenuating effect of vitamin E, as a natural antioxidant, against this toxicity. Thirty Albino rats were divided into 3 groups (n = 10): … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 72 publications
0
6
0
1
Order By: Relevance
“…Due to their exceptional antibacterial qualities, silver nanoparticles (Ag-NPs) are widely used in a variety of industries. However, numerous investigations have shown that Ag-NPs have the potential to be cytotoxic due to their impact on the excessive generation of reactive oxygen species (ROS) in various cells and pathological conditions like cancer [ 62 ]. Ag-NPs have strong antimicrobial properties against many fungi, viruses, and bacteria due to their activity as photocatalysts and their ability to produce reactive oxygen species [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to their exceptional antibacterial qualities, silver nanoparticles (Ag-NPs) are widely used in a variety of industries. However, numerous investigations have shown that Ag-NPs have the potential to be cytotoxic due to their impact on the excessive generation of reactive oxygen species (ROS) in various cells and pathological conditions like cancer [ 62 ]. Ag-NPs have strong antimicrobial properties against many fungi, viruses, and bacteria due to their activity as photocatalysts and their ability to produce reactive oxygen species [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Цитотоксичность наночастиц серебра при регулярном внутрисосудистом введении отмечалась и на клетках поднижнечелюстных слюнных желез. У лабораторных крыс, которым в течение 28 дней делали инъекции раствора наночастиц серебра, регистрировались дегенеративные изменения в ацинусах и протоках желез, что проявлялось в первую очередь в виде вакуолизации цитоплазмы [30].…”
Section: стоматологияunclassified
“…9 Excessive ROS production may disrupt cells' antioxidant defense mechanisms, leading to OS, inflammation, and ultimately cellular damage. 10 Given that antioxidants can neutralize ROS and reduce OS, 11 it is crucial to utilize them to mitigate the toxic effects of CuO-NPs and ensure their safe application.…”
Section: Introductionmentioning
confidence: 99%